Several Types of Totally Continuous Functions in Double Fuzzy Topological Spaces - Fatimah M. Mohammed; M. S. M. Noorani; A. Ghareeb (Advances in Fuzzy Systems)
We introduce the notions of totally continuous functions, totally semicontinuous functions, and semitotally continuous functions in double fuzzy topological spaces. Their characterizations and the relationship with other already known kinds of functions are introduced and discussed.